Huanglongbing (HLB; Citrus Greening) and Nutrient Deficiency Identification - Tripti Vashisth; Megan M. Dewdney; Jamie D. Burrow (EDIS)
Huanglongbing (HLB) is a bacterial disease that is spread by an insect, the Asian citrus psyllid. This 2-page fact sheet is a minor revision that explains how to tell the difference between HLB symptoms and symptoms from nutrient deficiencies. Written by Tripti Vashisth, Megan M. Dewdney, and Jamie D. Burrow, and published by the Plant Pathology Department, July 2019.